Antibacterial, antifungal, and anti-biofilm effects of sulfamethoxazole-complexes against pulmonary infection agents. (February 2023) - Siqueira, Fallon dos Santos; Siqueira, Josiéli Demetrio; Denardi, Laura Bedin; Moreira, Kelly Schneider; Lima Burgo, Thiago Augusto; de Lourenço Marques, Lenice; Machado, Alencar Kolinski; Davidson, Carolina Bordin; Chaves, Otávio Augusto; Anraku de Campos, Marli Matiko; Back, Davi Fernando
Abstract: Antibiotic resistance associated with pulmonary infection agents has become a public health problem, being considered one of the main priorities for immediate resolution. Thus, to increase the therapeutic options in the fight against resistant microorganisms, the synthesis of molecules from pre-existing drugs has shown to be a promising alternative. In this sense, the present work reports the synthesis, characterization, and biological evaluation (against fungal and bacterial agents that cause lung infections) of potential metallodrugs based on sulfamethoxazole complexed with Au I, Ag I, Hg II, Cd II, Ni II, and Cu II . The minimal inhibitory concentration (MIC) value was used to evaluate the antifungal and antibacterial properties of the compounds. In addition, it was also evaluated the antibiofilm capacity in Pseudomonas aeruginosa, through the quantification of its biomass and visualization using atomic force microscopy. For each case, molecular docking calculations were carried out to suggest the possible biological target of the assayed inorganic complexes. Our results indicated that the novel inorganic complexes are better antibacterial and antifungal than the commercial antibiotic sulfamethoxazole, highlighting the Ag I -complex, which was able to inhibit the growth of microorganisms that cause lung diseases with concentrations in the 2–8 μg mL −1 range, probably at targeting dihydropteroate synthetase – a key enzyme involved in the folate synthesis. Furthermore, sulfamethoxazole complexes were able to inhibit the formation of bacterial biofilms at significantly lower concentrations than free sulfamethoxazole, probably mainly targeting the active site of LysR-type transcriptional regulator (PqsR). Overall, the present study reports preliminary results that demonstrate the derivatization of sulfamethoxazole with transition metal cations to obtain potential metallodrugs with applications as antimicrobial and antifungal against pulmonary infections, being an alternative for drug-resistant strains. Graphical abstract: Image 1 Highlights: Sulfametoxazole metal transition complexes tested against antimicrobial. In vitro antimicrobial activity of sulfametoxazole and its derivative compounds. All complexes were evaluated in the face of antibiofilm activity. The complexes were tested molecular docking.